Testing the Fit of Cobb-Douglass Production Function Within Unrestricted Least Squares - Amuka, Joseph I.; Asogwa, Fredrick O.; Ugwu, Collins C.; Ugwu, Kelvin C. (International Journal of Economics and Financial Issues, 2018)
Criticisms trailed Cobb-Douglass production model and its constant returns to Scale assumption after its application in America Economy in 1927. Studies using restricted least squares approach to validate the model have produced different results in different economies. The question this paper tried to answer is this-without restriction, can Cobb-Douglass model still fit well in an economy’s production? We answered this question using unrestricted least squares method with quarterly data generated from Central Bank of Nigeria between 2009 and 2012. The study is very important in Nigeria where the economy has not performed well despite heavy government investment in the last two decades. Result from the shows that even without restriction, Nigeria economy displays constant returns to scale production, suggesting that the Cobb-Douglass Production Function fits well in Nigeria economy. The result has an implication for a country in which the economy is driven by the public sector. Keywords: Cobb-Douglass, Production Function, Constant Returns, Unrestricted Least Square JEL Classification: E23